If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (v + 5)(v + -18) = 0 Reorder the terms: (5 + v)(v + -18) = 0 Reorder the terms: (5 + v)(-18 + v) = 0 Multiply (5 + v) * (-18 + v) (5(-18 + v) + v(-18 + v)) = 0 ((-18 * 5 + v * 5) + v(-18 + v)) = 0 ((-90 + 5v) + v(-18 + v)) = 0 (-90 + 5v + (-18 * v + v * v)) = 0 (-90 + 5v + (-18v + v2)) = 0 Combine like terms: 5v + -18v = -13v (-90 + -13v + v2) = 0 Solving -90 + -13v + v2 = 0 Solving for variable 'v'. Factor a trinomial. (-5 + -1v)(18 + -1v) = 0Subproblem 1
Set the factor '(-5 + -1v)' equal to zero and attempt to solve: Simplifying -5 + -1v = 0 Solving -5 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1v = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1v = 0 + 5 -1v = 0 + 5 Combine like terms: 0 + 5 = 5 -1v = 5 Divide each side by '-1'. v = -5 Simplifying v = -5Subproblem 2
Set the factor '(18 + -1v)' equal to zero and attempt to solve: Simplifying 18 + -1v = 0 Solving 18 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1v = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -1v = 0 + -18 -1v = 0 + -18 Combine like terms: 0 + -18 = -18 -1v = -18 Divide each side by '-1'. v = 18 Simplifying v = 18Solution
v = {-5, 18}
| -4x+5y=-22 | | 7x+6+5x+3=3x-9 | | (9)y-6(y)= | | 56-4x=9-10x | | s/6+3=11 | | 143-4x=6x+13 | | 5(8-3p)=100 | | (8x-3)(2x^2-4x+4)=0 | | x=ay+b | | 5k^2+37k-24=0 | | 9yx-6yx= | | m^2+13m+12=0 | | 9q+1-9= | | 784=16t^2 | | 3(n-8)(3n-4)=0 | | 3-2(x+3)=X-8 | | w(w-5)=24 | | 3f(2)+f(2)*6=36 | | (15+3x)-3x= | | w^2=7w | | 6m+5n=-32 | | 4x-5=12x-45 | | 8x^3+36x^2+40x+12=0 | | 9d=27 | | -7x+9(-4)=-15 | | 56=8(x+3) | | -4+y=20 | | 7=s/2+5 | | (x*x)+(x*x)=2116 | | 10d+6=6d+22 | | X^2+bx+64= | | 122-2x=6x+16 |